Early Childhood Education as a Tool for Indigenous Language Preservation: A Comparative Study of Nepal and New Zealand (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
This comparative qualitative case study investigates the role of early childhood education in indigenous language revitalization efforts in Nepal and New Zealand through document analysis and non-participatory classroom observations. The study examines policy frameworks, classroom practices, teacher preparation, community engagement, and systemic challenges in both countries. Findings reveal a stark contrast: New Zealand’s well-established policies and programs, such as the immersive Kōhanga Reo centers, provide strong institutional support, specialized teacher training, and active community involvement that effectively sustain Māori language use and cultural identity from early childhood. In contrast, Nepal’s National Education Policy acknowledges the importance of mother tongue instruction but lacks enforceable implementation strategies, sufficient teacher training, and adequate resources, resulting in fragmented and symbolic language education efforts. Community engagement is inconsistent, and dominant languages like Nepali and English overshadow indigenous languages due to socio-economic pressures. The study highlights the urgent need for Nepal to adopt immersion-based early learning programs, institutionalize teacher training focused on indigenous languages, foster community ownership, and secure sustained policy backing and funding. Drawing lessons from New Zealand’s experience, this research emphasizes that early childhood education can be a critical platform for preserving linguistic heritage, provided that policies translate into culturally grounded practices and systemic support. This study offers strategic recommendations for strengthening indigenous language revitalization through education in Nepal and similar contexts worldwide.